Corporate Governance, culture and legal system: a state of the matter (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the present work we deal with the question of corporate governance, how this issue came into being and the main lines of research. We put an emphasis on the origins of the research in this area, paying particular attention to the culture where the firm is embedded as well as the cultures developed by the firm. Likewise we made areference to the importance of the legal systems which regulate the big modern enterprise. We conclude with the question if there is a convergence of corporate governance systems and even if that convergence is desirable.
Keywords: Corporate governance; culture; legal systems; systems of corporate governance; convergence of systems.